2020
DOI: 10.1016/j.redox.2020.101636
|View full text |Cite|
|
Sign up to set email alerts
|

Interleukin-22 deficiency alleviates doxorubicin-induced oxidative stress and cardiac injury via the p38 MAPK/macrophage/Fizz3 axis in mice

Abstract: Several interleukin (IL) family members have been demonstrated to be involved in doxorubicin (DOX)-induced cardiac injury. This study aimed to investigate the role of IL-22 in DOX-induced cardiac injury and explore its possible mechanisms. In this study, mice were given DOX, and the cardiac expression and sources of IL-22 were determined. Then, IL-22 was knocked out to observe the effects on DOX-induced cardiac injury in mice. In addition, the p38 mitogen-activated protein kinase (MAPK) pathway was inhibited, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…There is increasing evidence that Møs are one of the most important sources of oxidative stress‐related substances. In addition, Mø differentiation is closely related to oxidative stress levels, and M1 Mø differentiation can significantly exacerbate oxidative stress, while M2 Mø differentiation can significantly reduce oxidative stress 35–37 . The Nrf2 pathway is the most important pathway that regulates oxidative stress in a variety of complex pathological injury factors 24,38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that Møs are one of the most important sources of oxidative stress‐related substances. In addition, Mø differentiation is closely related to oxidative stress levels, and M1 Mø differentiation can significantly exacerbate oxidative stress, while M2 Mø differentiation can significantly reduce oxidative stress 35–37 . The Nrf2 pathway is the most important pathway that regulates oxidative stress in a variety of complex pathological injury factors 24,38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to mediating an immune response, these immune cells can also release a large number of inflammatory factors, including IFN, transforming growth factor, chemokines, and ILs [22][23][24]. Multiple ILs, including IL-6, IL-12, and IL-22, are primarily secreted by activated immune cells and are rarely or not secreted by nonimmune cells [25][26][27]. Unlike these ILs, large amounts of IL-16 are secreted by both immune cells and cells [5][6][7].…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…Recently, Ye et al reported that increased activation of the p65 pathway significantly increased M1 macrophage differentiation in both Ang II-infused and DOX-induced mice [26,27]. Nuclear p-p65 but not total p-p65 regulates the differentiation and inflammatory response of macrophages [27][28][29][30]. To determine the effects of IL-16 on p65 pathway activation, the p-p65 levels in both the cytoplasm and nucleus were mea-sured.…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…Under normal physiological conditions, prooxidant and antioxidant substances maintain a dynamic balance, which is essential for the maintenance of normal physiological activities [ 28 , 29 ]. Under the action of doxorubicin, Ang II, and other external pathogenic factors, this stable equilibrium relationship is broken, as evidenced by reductions in the levels of antioxidants, including NRf2, HO-1, and SOD, and increases in the levels of oxygen-promoting substances, including Nox2, Nox4, and MDA [ 30 , 31 ]. To determine whether IL-16 is involved in sepsis-induced cardiac injury through the regulation of oxidative stress, pathways and markers related to oxidative stress were detected.…”
Section: Discussionmentioning
confidence: 99%